Genetic analysis and prenatal diagnosis of recessive dystrophic epidermolysis bullosa caused by compound heterozygous variants of the COL7A1 gene in a Chinese family - Wang, Yu; Song, Zhen; Zhang, Lihua; Li, Na; Zhao, Jie; Yang, Ruifang; Ji, Shuhua; Sun, Ping (Frontiers in Pediatrics, 2022)
Background: Dystrophic epidermolysis bullosa (DEB) is an incurable and inherited skin disorder mainly caused by the mutations in the gene encoding type VII collagen (COL7A1). The purpose of this study was to identify the causative genetic variants and further perform genetic diagnosis in a Chinese family affected with DEB. Methods: High-throughput sequencing was performed to analyze the genetic skin disorders-related genes of parents of the proband, and the variants were further confirmed in the other members by Sanger sequencing. Sanger sequencing, karyotype analysis, and chromosomal microarray analysis (CMA) were used together for prenatal diagnosis after the second pregnancy. The phenotype of the fetus was tracked after the diagnosis and induction of labor. Moreover, skin and muscle pathological examination and whole-exome sequencing (WES) of the skin and muscle tissue of the induced fetus were performed. Results: Here we determined two heterozygous variants of the COL7A1 gene that contributed to the autosomal recessive DEB (RDEB) in the family, i.e. a novel pathogenic variant (c.8335G>T, p.E2779*) and a likely pathogenic variant (c.7957G>A, p. G2653R). Sanger sequencing of amniotic fluid cells showed that the fetus carried the above two compound heterozygous variants, and the karyotype analysis and CMA results showed no abnormality. The clinical phenotype and pathological results of the induced fetus were consistent with the characteristics of DEB. Further, WES analysis also confirmed a novel compound heterozygous variation in COL7A1, consisting of two variants, namely c.8335G>T and c.7957G>A in the fetus. Conclusions: This study expands the spectrum of disease-causing variants in COL7A1 and provides a theoretical basis for diagnosis, genetic counseling, and prognosis of families affected by RDEB.